Solve the differential equations using homogeneous equation.
1. ( 2y - x )dy/dx = 2x + y given that y=3 and x=2.
2. ( xy + y square) + ( x square - xy) dy/dx =0
1. (2y - x )y' = 2x + y
We use the substitution: y = xu, y' = u+xu', then
(2xu-x)(u+xu') = 2x+xu
"x\\frac{du}{dx}= \\frac{2+u}{2u-1}-u = \\frac{2+u - 2u^2+u}{2u-1} = -2\\frac{u^2-u-1}{2u-1}"
This is an equation with separable variables.
Consider one of the possible solutions - with constant functions u(x) such that u2-u-1=0
Then "u(x) = (1\\pm\\sqrt{5})\/2" and "y(x) = x(1\\pm\\sqrt{5})\/2".
These solutions do not satisfy to the initial condition y(2) = 3.
"\\frac{2u-1}{u^2-u-1}du = -\\frac{2}{x}dx=-2d(\\ln |x|)=-d(\\ln x^2)"
"\\frac{2u-1}{u^2-u-1}du = \\frac{d(u^2-u)}{u^2-u-1} = d(\\ln|u^2-u-1|)" , therefore,
"d(\\ln(x^2|u^2-u-1|))=0"
"d(x^2(u^2-u-1))=0"
"x^2(u^2-u-1)=c"
"u^2-u-1=cx^{-2}"
"y^2-xy-x^2=c"
"c=y(2)^2-2y(2)-2^2=9-6-4=-1"
"y^2-xy-x^2+1=0"
"y=(x\\pm\\sqrt{5x^2-4})\/2"
"3 = y(2) = (2\\pm 4)\/2" , therefore, one should choose the sign "+".
Answer. "y=(x+\\sqrt{5x^2-4})\/2"
2. "( xy + y^2) + ( x^2 - xy) dy\/dx =0"
We use the substitution: y = xu, y' = u+xu', then
"x^2( u + u^2) + x^2 (1 - u) (u+xu') =0"
"2u+x(1-u)u' = 0"
"u=0" or "\\frac{u-1}{2u}du = \\frac{dx}{x}"
"y=0" or "u\/2 -\\ln|u|=\\ln|x|+c"
"y=0" or "y\/(2x) -\\ln|y| = c"
"y=0" or "y -x\\ln y^2 = 2cx"
Answer. "y=0" or "y -x\\ln y^2 = 2cx"
Comments
Leave a comment